TINDAK TUTUR ILOKUSI DALAM ACARA GOYANG JEMBER DI RADIO PROSALINA FM - NFN Santuso; Akhmad Sofyan; Agustina Dewi Setyari (Jurnal Ilmiah SEMANTIKA, 2023)
This research aims to describe the illocutionary speech acts performed between the announcer and callers in the "Goyang Jember" (Gober) program. This research is expected to be beneficial in understanding the factors that cause a mass media program to have many followers, particularly in terms of language aspects. This research falls under the category of qualitative descriptive research. The research data consists of words, phrases, clauses, and sentences uttered by the announcer and 20 different callers. The data source for this research is taken from the conversations between the announcer and callers in September 2022, which were uploaded on the Prosalina FM YouTube account. The data collection stage uses the observation method with the technique of non-participant observation and note-taking. The data analysis stage employs the pragmatic equivalence method. Based on the results of the data analysis, it was found that the conversations between the announcer and callers contain five types of illocutionary speech acts, namely assertive, directive, expressive, commissive, and declarative. The most dominant speech act is the assertive speech act. This is because Gober is a relaxed program that allows listeners to have casual conversations or small talk with the announcer through phone calls. The declarative speech act is the least frequently used. The other forms of speech acts are quite often used as variations in the discourse to make the conversation warm, more friendly, maintain politeness, create a pleasant atmosphere, and avoid boredom.